Time to rethink the law on part-human chimeras. Issue 1 (15th May 2019) - Koplin, Julian J; Savulescu, Julian
Abstract: It may soon be possible to generate human tissues and organs inside of part-human chimeras via a technique known as interspecies blastocyst complementation. Using Australian legislation as a case study, we show why this technique of creating part-human chimeras falls within the gaps of existing legislation. We give an overview of the key ethical issues raised by part-human chimera research, and we describe how well these issues are met by a range of possible regulatory approaches. We ultimately argue that regulation of part-human chimera research should be (re)designed to balance two key aims: to facilitate ethical research involving part-human chimeras and to prevent unethical experimentation with chimeras that have an uncertain—and potentially substantial—degree of moral status.